Impact of esophageal cancer staging on overall survival and disease-free survival based on the 2010 AJCC classification by lymph nodes - Li, Qun (Oxford University Press, 2013)
This retrospective study investigated the effect of modifications presented in the seventh edition of the American Joint Committee on Cancer (AJCC) Manual for staging esophageal cancer on the characterization of the effectiveness of post-operative chemotherapy and/or radiotherapy, as measured by overall and disease-free survival. The seventh edition of the AJCC Manual classifies the number of lymph nodes (N) positive for regional metastasis into three subclasses. We used the AJCC classification system to characterize the cancers of 413 Chinese patients with esophageal cancer who underwent radical resection plus regional lymph node dissection over a 10-year period. The 10-year survival rate was 14.3% for stage N1 patients and 6.1% for stage N2 patients. Only one stage N3 patient was followed >4 years (53.4 months). The 10-year disease-free rate was 13.6% for stage N1 patients. Patients with stage N2 or N3 cancer were more likely to have tumor recurrences, metastases or death than patients with stage N1 cancer. Post-operative radiotherapy provided no survival benefit, and may have had a negative effect on survival. In this study, the N stage of esophageal cancer was an independent factor affecting overall and disease-free survival. Our results did not clarify whether or not radiotherapy after radical esophagectomy offers any survival benefit to patients with esophageal cancer.